Moral and spiritual leadership in an age of plural moralities - Alma, Hans; Avest, Ina ter (Studies in world Christianity and interreligious relations, 2019)
Theoretical perspectives -- Toward a relational ethic / Kenneth J. Gergen -- Dialogical self theory in a boundary-crossing society / Hubert J.M. Hermans -- Religion, radicalism, relativism : between social identity and dialogical self theory / Frans Wijsen -- Plural moralities and the search for meaning / Hans Alma -- Developing theory and practice in dialogue -- Leadership in an age of plural moralities -- Provocative guidance : a practice of narrative leadership / Ina ter Avest -- Dialogical leadership : leading yourself across boundaries of self and culture / Rens van Loon and Angel S. Buster -- Developing intercultural sensitivity in a world of multicultural identities / Jutta König -- Education in an age of plural moralities -- Plural British values : between generosity and fear / Julia Ipgrave -- Life orientation as part of professional development : moral leadership of professionals from a DST-perspective / Edwin van der Zande and Cok Bakker -- Moral commitment and existential issues in religious and worldview education / Geir Skeie -- Citizenship in an age of plural moralities -- The culturalization of citizenship in the Netherlands: towards cosmopolitan sociabilities in a neoliberal epoch / Toon van Meijl -- Beyond the boundaries : overcoming resentments, resistance and revulsion / Mary Gergen -- Orientation, disorientation, and reorientation in the context of plural moralities : experiences of an LGBT refugee arriving in the Netherlands / Carmen Schuhmann and Robin Knibbe -- Epilogue / Hans Alma and Ina ter Avest -- Index.